Early Childhood Language Development: Factors, Theoretical Perspectives, and Educational Implications - Selvia Rahma Dewi; Randi (JPI: Jurnal Pustaka Indonesia, 2024)
Language development in children represents a critical foundation for cognitive, social, and academic growth, yet it is highly influenced by biological, environmental, and socio-cultural factors that can either support or hinder progress. This study aimed to analyze theories, stages, and determinants of children’s language development and to identify potential barriers that may impede optimal growth. Using a qualitative descriptive design based on a systematic literature review, data were collected from books, journal articles, and credible reports, which were then synthesized through thematic analysis to capture key concepts and patterns. The results reveal that language development progresses through identifiable stages—from babbling and single words to complex sentences—and is strongly shaped by interaction with caregivers, enriched literacy environments, and exposure to social communication. At the same time, obstacles such as limited parental engagement, socioeconomic disparities, and neurodevelopmental risks were found to negatively affect linguistic competence. The discussion emphasizes that language development is not only a linguistic and cognitive process but also a socio-cultural phenomenon requiring integrative support from families, educators, and policymakers. The implication of this research is that holistic strategies combining play-based learning, dialogic reading, parental involvement, and inclusive early education policies are essential for fostering equitable and sustainable language growth among children.